State land supervision system and low-carbon transformation of agriculture: a quasi-natural experiment from China’s routine land inspections - Qian, Jingjing; Xu, Ning (Frontiers in Environmental Science, 2024)
As a high-intensity, high-standard institutional mechanism in land supervision and management, the State Land Supervision System (SLSS) plays a crucial role in deterring land-related violations, enforcing farmland protection, ensuring national food security, and facilitating sustainable agricultural development. However, previous research has seldom examined how the SLSS contributes to the low-carbon transformation of agriculture (LCTA). This study treats China’s routine land inspections as a quasi-natural experiment, utilizing panel data from 283 prefecture-level and higher cities from 2005 to 2016 to empirically analyze whether and how the SLSS supports LCTA. The findings reveal that the SLSS significantly advances LCTA, with the low-carbon agricultural development level in inspected cities increasing by approximately 2.17%. The SLSS promotes LCTA primarily through enhancing agricultural technological progress and encouraging agricultural scale operations. Compared to major grain-producing regions, high-poverty areas, and regions under significant fiscal pressure, the SLSS more effectively fosters LCTA in non-grain-producing areas, regions with lower poverty rates, and areas facing less fiscal strain. Furthermore, the SLSS has a more pronounced effect on advancing low-carbon agricultural development in cities that already demonstrate higher levels of low-carbon progress. This study provides novel empirical evidence regarding the environmental impacts of SLSS in the agricultural sector, offering insights relevant to the pursuit of agricultural modernization.